Krasnyi kvadrat . Krasnyi kvadrat . Red Square Box . Красный квадрат - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Discussion of a revolution as a phenomenon and of a current political situation in Russia; interviews with people on the street about the election campaign. Featured in the program: Shokhin, Aleksandr (Vice Prime Minister of the Russian Government); IAvlinskii, Grigorii Alekseevich (Politician); Ziuganov, Gennadii Andreevich (Politician) Contributors: Molchanov, Denis (Anchor) Обсуждение революции как явления и текущей политической ситуации в России; интервью с людьми на улице о предвыборной кампании. В программе участвуют: Шохин, Александр (Вице-премьер правительства России); Явлинский, Григорий Алексеевич (Политик); Зюганов, Геннадий Андреевич (Политик) Создатели: Молчанов, Денис (Ведущий/Ведущая)